Trends in Mobile Marketing - Chocholová, Petra (2011)
The principal aim of this thesis is to assess the state of the mobile marketing as of the first quarter of 2011 and to discuss various scenarios of the future development. This thesis defines the terms "mobile marketing" and "mobile advertising" and identifies the main players in the industry. It explores the main categories of mobile advertising such as mobile messaging, in-content and mobile internet advertising. Later, it analyzes the latest trends in the industry and describes in detail the advancements in QR tagging, location based advertising and augmented reality.